2010
DOI: 10.1063/1.3486216
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio prediction of magnetically dead layers in freestanding γ-Ce(111)

Abstract: It is well known that the surface of nonmagnetic α-Ce is magnetically ordered, i.e., γ-like. One then might conjecture, in agreement with previous theoretical predictions, that the γ-Ce may also exhibit at its surfaces even more strongly enhanced γ-like magnetic ordering. Nonetheless, our result shows that the (111)-surfaces of magnetic γ-Ce are neither spin nor orbitally polarized, i.e., α-like. Therefore, we predict, in contrast to the nonmagnetic α-phase which tends to produce magnetically ordered γ-like th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 55 publications
2
2
0
Order By: Relevance
“…Hence, the structure of uranium can cause to reverse the magnetic properties from its bulk to its surfaces and inversely from its surfaces to its bulk. Similar results were recently reported 14 for the isostructural αand γ-Ce systems.…”
Section: Magnetic Properties and Electronic Structuressupporting
confidence: 91%
See 1 more Smart Citation
“…Hence, the structure of uranium can cause to reverse the magnetic properties from its bulk to its surfaces and inversely from its surfaces to its bulk. Similar results were recently reported 14 for the isostructural αand γ-Ce systems.…”
Section: Magnetic Properties and Electronic Structuressupporting
confidence: 91%
“…Stojić and coworkers employing the FP-augmented plane waves (FP-APW) method have shown that the α-U compound is a nonmagnetic system in its bulk form, whereas it behaves as a magnetic system with the imposed spin MM of 0.84µ B at its freestanding surfaces 11 . A typical substrate can affect the structure 13 and magnetism 14 of the overlayers that can give rise to a variety of lattice mismatches and as a result to various U-U interlayer (IL) spacings (ILSs). The U-U spacing can change the degree of 5f localizations and thereby electronic structures.…”
Section: Introductionmentioning
confidence: 99%
“…Dependence of the lattice parameter to the correlations among 4f-electrons is in agreement with the previous results for the isostructural α - and γ -Ce compounds. The GGA + U with U eff = 4.4 eV (PBE-GGA) predicts 35 the larger (smaller) lattice parameter of the fcc γ -Ce ( α -Ce) in agreement with experiment. The B3LYP with α = 0.2 lattice parameter is larger and bulk modulus is smaller than those of GGA + U.…”
Section: Computational Detailssupporting
confidence: 68%
“…31 The exchangecorrelation effects are calculated within the local density approximation (LDA), 32 generalized gradient approximation (GGA), 33 GGAsol, 34 Wu-Cohen GGA (WC-GGA), 35 meta GGA (m-GGA) 36 and hybrid functional B3PW91 37,38 with spin polarization. As lanthanides are strongly correlated systems with localized 4f electrons, 39,40 to obtain the exact nature of the electronic structure of the compounds under consideration, we used LDA + U and GGA + U methods. The DFT + U method is based on the Hubbard model, which treats the strongly correlated electron systems with an orbital dependent potential of Coulomb and exchange interactions.…”
Section: Methods Of Calculationsmentioning
confidence: 99%